A importância do mapeamento das redes de conhecimento para a gestão da informação e do conhecimento em ambientes esportivos: Um estudo de caso no Marília Atlético Clube - Jorge, Carlos Francisco Bitencourt [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (FapUNIFESP (SciELO), 2016)
The construction of networking knowledge enables the best use for the process of Information Management (IM) and Knowledge Management (KM). It is important to consider the mapping of informational sources and information flows, a solid basis for the IM and KM. The mapping of networking knowledge in low perception with respect the importance of information and knowledge, enables demonstrate to organizational individuals the importance of information and knowledge for the performance of processes, activities and tasks. The soccer clubs do not have a culture of valuing and use of information and knowledge structured mode. From this perspective, emphasize the importance of individuals in GI and GC processes in soccer clubs, propitiates available through a Sociogram, the relationships and the key sources for the effectiveness of IM and KM. The research was carried in Marilia Athletic Club (MAC), Club Soccer of Marilia City, Sao Paulo State, Brazil. It was identified that the information is centralized in a few people as demonstrated by the Sociogram. The complex situation evidence that individuals act for a specified time at the Club, influencing the commitment management processes developed in the club.
The importance of mapping knowledge networks for information management and knowledge in sports environment: A case study in Marilia Athletic Club
Keywords: Information management; Knowledge management; Knowledge networks; Marilia athletic club; Soccer clubs